2006
DOI: 10.1111/j.1365-2699.2005.01381.x
|View full text |Cite
|
Sign up to set email alerts
|

Did lemurs have sweepstake tickets? An exploration of Simpson's model for the colonization of Madagascar by mammals

Abstract: The fossil records of the living orders of mammals do not extend much earlier than the latest Cretaceous/early Palaeocene (Alroy, 1999;Foote et al., 1999). If this evidence indeed reflects the time of origin of the orders, rather than indicating the inadequacy of the fossil record (Martin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 56 publications
0
51
0
1
Order By: Relevance
“…Stankiewicz et al [2006] demonstrated that flotsam velocity stabilizes at the value corresponding to the surface current velocity within hours. The directions of the present currents and winds that characterize the Mozambique Channel are not conducive to successful dispersal events from Africa to Madagascar [Masters et al, 1995;Stankiewicz et al, 2006], although dispersal in the opposite direction can be achieved within 10 days [Stankiewicz et al, 2006]. This situation is likely to have prevailed for at least the last 50 million years, when India docked with Asia, setting up the major Indian Ocean circulation pattern.…”
Section: Foliamentioning
confidence: 99%
See 1 more Smart Citation
“…Stankiewicz et al [2006] demonstrated that flotsam velocity stabilizes at the value corresponding to the surface current velocity within hours. The directions of the present currents and winds that characterize the Mozambique Channel are not conducive to successful dispersal events from Africa to Madagascar [Masters et al, 1995;Stankiewicz et al, 2006], although dispersal in the opposite direction can be achieved within 10 days [Stankiewicz et al, 2006]. This situation is likely to have prevailed for at least the last 50 million years, when India docked with Asia, setting up the major Indian Ocean circulation pattern.…”
Section: Foliamentioning
confidence: 99%
“…The likelihood of traversing a vast expanse of ocean may have been increased in the Mozambique Channel by means of island-hopping across putative islands emergent along the DFZ from the Mid-Eocene to Early Miocene [McCall, 1997], and in the South Atlantic by shallower waters above the Mid-Atlantic Ridge and the Ceara and Sierra Leone Rises [Murray, 2001]. Murray's hypothesis is more likely in terms of the current and wind directions in the Mozambique Channel [Stankiewicz et al, 2006] and in the South Atlantic [Houle, 1999], but does not explain the absence of close relationships between the Malagasy and African taxa [Sparks and Smith, 2004, . Finally, even given the presence of 'stop-over points' along the way, the Mozambique Channel and Indian Ocean hardly qualify as 'minor saltwater barriers' [Briggs, 2003], neither does the South Atlantic pose 'a modest saltwater gap' [Briggs, 2003].…”
Section: Freshwater Fishesmentioning
confidence: 99%
“…However, present ocean currents allow for dispersal from Madagascar to Africa, but oppose reciprocal dispersal from Africa to Madagascar across the Mozambique Channel. If ocean currents were the same for most of the Cenozoic as they are today, they would not have facilitated west to east transoceanic dispersal across the Mozambique Channel because of the strong south -southwest flow of the Mozambique Current [153].…”
Section: The Importance Of Dispersalmentioning
confidence: 99%
“…Most authors have ignored the problem and many continue to propose dispersal events for which there is no known analogue in the current ecology. For example, it is still widely believed that primates rafted across vast areas of open ocean (Fleagle, 1999), although this has never been observed (Stankiewicz et al, 2006, andMasters et al, 2007, have provided good critiques). Biologists have come to accept the idea that distribution and dispersal are often mysterious and paradoxical.…”
Section: Darwin Wrotementioning
confidence: 99%